2022
DOI: 10.1155/2022/6577942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crucial lncRNAs for Luminal A Breast Cancer through RNA Sequencing

Abstract: Background. The growing body of evidence indicates aberrant expression of long noncoding RNAs (lncRNAs) in breast cancer. Nevertheless, a few studies have focused on identifying key lncRNAs for patients with luminal A breast cancer. In our study, we tried to find key lncRNAs and mRNAs in luminal A breast cancer. Methods. RNA sequencing was performed to identify differentially expressed mRNAs (DEmRNAs) and differentially expressed lncRNAs (DElncRNAs) in luminal A breast cancer. The protein-protein interaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Consequently, whether these lncRNAs also affect SMCs has not yet been investigated. MIR222HG was also described in association with cancer 36 , 37 but also with macrophage polarisation 38 . In this context, it is to be noted that SMCs can adopt various phenotypes, including also that of macrophages or foam cells 39 .…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, whether these lncRNAs also affect SMCs has not yet been investigated. MIR222HG was also described in association with cancer 36 , 37 but also with macrophage polarisation 38 . In this context, it is to be noted that SMCs can adopt various phenotypes, including also that of macrophages or foam cells 39 .…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, whether these lncRNAs also affect SMCs has not yet been investigated. MIR222HG was also described in association with cancer 34,35 but also with macrophage polarisation 36 . In this context, it is to be noted that SMCs can adopt various phenotypes, including also that of macrophages or foam cells 37 .…”
Section: Discussionmentioning
confidence: 98%
“…Extensive studies have reported that the majority of lncRNAs are abnormally expressed in tumor tissues, and each lncRNA exerts its function through different mechanisms in cancers [ 18 ]. According to the previous studies, LINC00968 was upregulated in osteosarcoma and lung squamous cell carcinoma and was downregulated in BC [ 14 , 16 , 17 , 19 ]. Also, this lncRNA combined with MIAT and LIN01140 lncRNAs can be used as potential diagnostic biomarkers for BC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has indicated the downregulation of LINC00968 in plasma of patients with BC and GEO datasets [ 16 ]. Another study has reported that LINC00968 is downregulated in luminal A BC [ 17 ]. The potential role of LINC00968 in luminal A and B subtypes of BC remains unexplored.…”
Section: Introductionmentioning
confidence: 99%